Patient Recommendations for Shared Decision-Making in Uterine Fibroid Treatment Decisions. (October 2021) - Riggan, Kirsten A.; Stewart, Elizabeth A.; Balls-Berry, Joyce E.; Venable, Sateria; Allyse, Megan A.
Uterine fibroids are noncancerous tumors associated with significant morbidity among symptomatic patients. While medical and surgical treatments have expanded, hysterectomy remains common. We interviewed women diagnosed with uterine fibroids ( n  = 47) to explore their experiences and recommendations for shared decision-making. A majority were non-Hispanic Black, highly educated (51.1%), and had graduate degrees (40.4%). Participants with both positive and negative provider experiences expressed a desire for a more proactive therapeutic approach, including a presentation by their provider of the spectrum of medical and surgical treatment options, and greater provider recognition of the impact of symptoms on quality of life. Women advocated for expanded shared decision-making that acknowledged their contribution to their own treatment plan and felt early screening and improved patient/provider education of uterine fibroid symptoms would facilitate greater congruence between treatment approaches and patient goals. Perceptions of insufficient input into their treatment plans frequently served as a barrier to care-seeking and treatment acceptance among women with uterine fibroid symptoms. Improved discussion of treatment options in the context of the unique symptom burden and values of the patient may facilitate greater provider trust and acceptance of uterine fibroid treatment.